A scoping review protocol on childhood immunization reminder strategies available to parents in Canada and the United States of America - Matilda Anim-Larbi; Vivian Puplampu; Sithokozile Maposa; Akram Mahani; Mary Chipanshi (PLoS ONE, 2025)
Introduction Vaccine-preventable diseases continue to cause morbidity and mortality despite the introduction of childhood immunizations. Recent media reports from Canada and the United States of America (USA) have highlighted a rise in childhood illnesses like measles, which could have been prevented with vaccines. Parents play a pivotal role in ensuring their children receive timely vaccinations. Immunization reminders can help parents who forget or miss vaccination appointments. In the USA, current literature indicates that Black children have lower vaccination rates than other racialized children and vaccine reminders may improve measles vaccine uptake among Black parents. However, there is limited data in Canada on vaccine uptake in children of Black parents, with evidence suggesting vaccine hesitancy among the Black population. Objective This scoping review aims to map out existing literature on immunization reminder strategies among parents to identify their impact in improving childhood vaccination rates and promoting child health. Inclusion criteria The review will include studies conducted in Canada and the United States of America that focus on immunization reminders for parents who have children under six years and published in English between 2015 and 2025. Methods Database and hand-searching of journals and gray literature will be carried out to retrieve pertinent articles. Studies that meet the inclusion criteria will be eligible for selection. The process of selecting eligible studies will then be summarized on a PRISMA-ScR chart. Collated in data-extraction tables will be authorship information, publication date, methods and findings. The findings, key arguments and themes will be analyzed using a thematic analysis and summarized using a narrative summary. Conclusion This review will contribute to the existing knowledge on parental preferences for vaccine reminder strategies and their usefulness in increasing childhood vaccination rates. The findings will inform and improve public health strategies aimed at boosting vaccine uptake among children.